Sharjah’s efforts in promoting the tourism sector - Alketbi, Abdalla; Abou-Shouk, Mohamed (Al-Adab Journal, 2024)
The study addressed the issue of tourism promotion and its impact on supporting the tourism sector, through an applied study on the Emirate of Sharjah and showing the extent of the efforts made by the Sharjah government to develop and develop the tourism sector. The problem of the study addressed how there is an active and effective tourism movement in the region that leads to supporting the emirate’s public income and marketing it on platforms. Tourism and an attempt to make Sharjah an attractive tourist area, along with how to achieve administrative activities and operations that attract tourists in the desired manner. It also addressed the importance of the scientific study in terms of considering the study a reference for researchers and support for scientific libraries, as well as the practical importance in explaining the role of tourism promotion in supporting the tourism sector in the Emirates and Sharjah. The objectives of the study were also to know the reality of tourism in the country, fill the deficiencies and deficiencies in the tourism process, and introduce effective means of promotion. The study also concluded with some results, including the weakness of tourism activity during the summer period in the country due to the climate that is not suitable for tourism. The most important recommendations were to carry out studies anticipating the future of the tourism sector by conducting strategic planning that ensures the flow of tourists throughout the year.